Improving in the antibacterial activity and the antioxidant properties of chemically modified extracts of Zinnia peruviana - Mohamed, Ana Mariel (2017)
In the present work we investigate the changes in the antibacterial activity and the antioxidant properties of modified extracts of Zinnia peruviana (L.) L. campesterol, stigmasterol and β-sitosterol were identified as majortriterpenoids in the natural extract, by CG-EIMS and NIST Mass Spectrometry Data Center. The acetonic extract was chemically modified by reactions of acid hydrolysis, sulfonylation, acetylation, methylation and silylation. The in-vitro antibacterial activity was evaluated against Gram-positive and Gram-negative bacteria. The acetonic extract showed significant activity only against Gram-positive bacteria (MIC/MBC = 2/9 mg/mL). The hydrolyzed extract improve the bioactivity to both, Gram-positive and Gram-negative (MIC/MBC = 2/8 mg/mL). Selectively, the acetylated extract was only effective toward Staphylococcus (MIC/MBC = 7/7 mg/mL). The tosylated extract was active against Gram-positive and P. aeruginosa (MIC/MBC = 24/24 mg/mL) and the silylated against Grampositiveand E. coli. (MIC/MBC = 15/15 mg/mL). The antioxidant activity was determining by DPPH and ABTS assays. Hydrolyzed extract increased the antioxidant properties (DPPH, IC50,(mg/mL) = 0.077 ± 0.007; ABTS IC50,(mg/mL) = 0.032 ± 0.005). The acylated and alkylated extracts reduce the bioactivity and silylated derivative eliminated the bioactivity. These results could be considered as a possible strategy to obtain antimicrobial agents from herbal medicines.